Dense, mixed-use, walkable urban precinct to support sustainable transport or vice versa? A model for consideration from Perth, Western Australia. Issue 1 (2nd January 2017) - Hendrigan, Cole; Newman, Peter
ABSTRACT: Within the majority of the literature on sustainable transport, it is accepted as ideal to arrange new urban growth in close proximity to major public transit services. While the literature on this subject of transit-oriented developments (TOD) is positive and optimistic, for the most part such assertions are conjectural. This article will attempt to fill this gap by revealing a modeling process undertaken for a local area's reurbanization project to understand the potential and limitations of several modes of transport to support the increased activity density in the precincts. Several of the most standardized policy levers were employed, such as parking ratios and mix of use and building height, and contrasted with the trip generation and transit mode's hourly capacity to reveal potential real-estate yields. The outcomes indicate not only the immediate yields but also the capacity for urban transformation due to each level of sustainable transport investments. The model is unique in that the capacity, parking ratios, and assumptions are highly transparent.